SEJARAH TRADISI FILSAFAT HELLENISTIK DALAM ISLAM - Irwan Ahmad Akbar (Jurnal Paradigma, 2020)
The purpose of this research is to answer how the Greek Hellenistic philosophical tradition can develop into the Islamic world. This research is a descriptive-analytic study of historical data (historical-ontological study). So this research has the conclusion that: Hellenistic philosophical tradition can develop in the world of Islam due to the wide expansion in the areas around Arabia that Islam did, including: during the S}a>h}a>bah era where they found the Alexandria library in Egypt, the Umayyads who tended to use the works - Ancient Greek works of practical science, such as medicine and astronomy. It was only during the time of the Abbasids that there was a massive translation of almost all ancient Greek works, especially philosophy. It was at that time that the Hellenistic philosophical tradition in the Islamic world stood at its peak.